Graduate Study with Online Education in the Post-Pandemic Era: An Experiential Case Study - Baskoro, Gembong; Sarwono, Edhie; Handajani, Endang Tri; Hendriana, Dena (KnE Social Sciences, 2024)
It is important for the human resources industry to have the ability to overcome existing industrial challenges as well as to prepare for the coming challenges impacted by the changing strategic environment. This includes but is not limited to Industry 4.0, VUCA & BANI World, the COVID-19 pandemic, Society 5.0 and changing geopolitics. To be able to deal with more complex problems requires Higher-Order Thinking Skills (HOTS). Therefore, improving HOTS, especially in the human resources industry, requires a solid partnership between industry and academia. The academic partnership will be meaningful in improving HOTS’s ability through a tailored master’s program known as a multi-disciplinary master’s program (MDMP). MDMP improve the HOTS of industry human resources by combining the strengths of academics and industry. This is an action research developed together between industry and academia and performed in several academic projects towards a master’s degree in various fields. It was concluded, based on the results, that MDMP showed promising results toward the improvement of industry human resources, especially in the ability of HOTS. Keywords: higher-order thinking skills, academic-industry partnership, multi disciplinary master’s program